2011
DOI: 10.1039/c0cp02805c
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate-stabilized Pt nanoparticles and their electrocatalytic activities

Abstract: The synthesis of long-term stable polyoxometalate (POM)-stabilized Pt nanoparticles (NPs) is described here. By means of controlled bulk electrolysis, the reduced POM anions, SiW(12)O(40)(4-) (or SiW(12)) and H(2)W(12)O(40)(6-) (or H(2)W(12)), respectively, served the dual role of reductant and protecting/stabilizing ligand for the Pt NPs. Transmission electron microscopy (TEM) images confirmed the formation of 3 to 4 nm sized Pt NPs, which coincidently was in the same size range of the commercial Pt black tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Thus, we would expect the stability provided by HPA that has been observed by others 17,20,24,32 to also aid in the uniform spatial distribution of Pt in this case, due to the support functionalization. This can be seen to some extent in the lower magnification TEM images (Supporting Figure 3, 31 ), but the argument is fairly subjective.…”
Section: Impact Of Siwmentioning
confidence: 71%
“…Thus, we would expect the stability provided by HPA that has been observed by others 17,20,24,32 to also aid in the uniform spatial distribution of Pt in this case, due to the support functionalization. This can be seen to some extent in the lower magnification TEM images (Supporting Figure 3, 31 ), but the argument is fairly subjective.…”
Section: Impact Of Siwmentioning
confidence: 71%
“…It has been confirmed that the introduction of POM into hybrid structures was beneficial to proton conduction and electrocatalytic activity [66][67][68]. Previous studies also illustrated that there were strong hydrogen bonding or ionic interaction between POMs and graphene, making it promising for selective detection of biomolecules or even in accurate evaluation for metabolic levels of intracellular biomolecules [69,70]. Herein, by using classical Keggin type polyoxometalate of dodecamolybdophosphate acid and 3DGF, an ultrastable and highly selective GCE modified with POM@3DGF hybrid was successfully fabricated and used as new type biosensor to detect cellular Xan and Gua simultaneously for the first time.…”
mentioning
confidence: 74%
“…[6,7] Mbomekalle and co-workers published several works reporting the application of several pristine POMs (Cu(II)- [25] and Mn(II)- [26] substituted polyoxoanions) as ORR electrocatalysts and promising results were obtained, with significant positive shifts in potentials of oxygen reduction, that occurs in the potential range E =-0.5 to 0.0 V (vs. Ag/AgCl) accordingly with the POM employed. As cocatalysts, the combination of POMs with a porphyrin [6] and Au, [7] Pd [27] and Pt [28,29] nanoparticles (NPs) was also described, resulting in enhanced ORR performances with a significant positive shift of the ORR potential for E = 0.5 -0.7 V (vs. Ag/ AgCl).…”
Section: Introductionmentioning
confidence: 99%